Interim Storage of the Dalat Nuclear Research Reactor: Radiation Safety Analysis - Kien-Cuong Nguyen; Vinh-Vinh Le; Ton-Nghiem Huynh; Ba-Vien Luong; Nhi-Dien Nguyen; Hoai-Nam Tran (Science and Technology of Nuclear Installations)
Radiation safety analysis of a new interim storage of the Dalat Nuclear Research Reactor (DNRR) for keeping spent high enriched uranium (HEU) fuel bundles during the core conversion to low enriched uranium (LEU) fuel had been performed and presented. The photon source and decay heat of the spent HEU fuel bundles were calculated using the ORIGEN2.1 code. Gamma dose rates of the spent fuel interim storage were evaluated using the MCNP5 code with various scenarios of water levels in the reactor tank and cooling time. The radiation safety analysis shows that the retention of 106 spent HEU fuel bundles at the interim storage together with a core of 92 LEU fuel bundles meets the requirements of radiation safety. The results indicate that in the most severe case, i.e., the complete loss of water in the reactor tank, the operators still can access the reactor hall to mitigate the accident within a limited time. Particularly, in the control room, the dose rate of about 1.4 μSv/h is small enough for people to work normally.